Characterizing Viscoelasticity of Corneal Stromal Models Using Non-Contact Air-Pulse Optical Coherence Elastography (OCE) and Validating Using Ramp–Hold Relaxation Testing - Yilong Zhang; Zhengshuyi Feng; Zhihong Huang; Chunhui Li (Photonics)
Corneal biomechanical properties are closely related to the cornea’s physiological and pathological conditions, primarily determined by the stromal layer. However, little is known about the influence of corneal cell interaction on the viscoelasticity of the stromal extracellular matrix (ECM). In this study, collagen-based hydrogels incorporated with keratocytes were reconstructed as corneal stromal models. Air-pulse optical coherence elastography (OCE) was used to characterize the viscoelastic properties of the corneal models. Plate compression, ramp–hold relaxation testing was performed on the initial corneal models. The findings demonstrated that the elastic modulus increased 5.27, 2.65 and 1.42 kPa, and viscosity increased 0.22, 0.06 and 0.09 Pa·s in the stromal models with initial collagen concentrations of 3, 5, and 7 mg/mL over 7 days. The elastic modulus and viscosity exhibited high correlation coefficients between air-pulse OCE and ramp–hold relaxation testing, with 92.25% and 98.67%, respectively. This study enhances the understanding of the influence of cell–matrix interactions on the corneal viscoelastic properties and validates air-pulse OCE as an accurate method for the mechanical characterization of tissue-engineered materials.